Study on cycle-by-cycle variations in a diesel engine with dimethyl ether as port premixing fuel. (1st April 2015) - Wang, Ying; Xiao, Fan; Zhao, Yuwei; Li, Dongchang; Lei, Xiong
Highlights: Cyclic variations of diesel engine with DME as premixing fuel were examined. Coefficients of cyclic variations of main combustion parameters were determined. Port DME quantity drastically influenced cyclic variations of DME-diesel engine. Cyclic variations in maximum in-cylinder pressure increased with a rise of DME. Abstract: Cycle-by-cycle variations in some parameters of the combustion and performance during a dual-fuel premixed charge compression ignition (PCCI) combustion process were investigated on a modified direct injection diesel engine with dimethyl ether (DME) as premixing fuel. Experiments were conducted under the two different loads with the different DME quantities at a constant engine speed (1700 r/min). Data of in-cylinder pressure of 100 consecutive combustion cycles for each test condition were recorded. The cycle-by-cycle variations of the maximum pressure ( p max ), the maximum mass-averaged temperature ( T max ), the maximum rate of pressure rise (( dp / dφ )max ), the maximum rate of heat release ( dq / dφ )max and the indicated mean effective pressure (IMEP) were analyzed and evaluated using the coefficient of variation (COV) of each parameter. The results show that both COVpmax (<3%) and COVTmax (<3%) are rather small with the different DME quantities. The varying trend of ( dp / dφ )max is similar to that of ( dq / dφ )max . The COVs of ( dp / dφ )max and ( dq / dφ )max decrease slightly but then increase with an increase in DME quantity. With a large DME quantity, a relatively wide range of cycle-by-cycle variations in IMEP and a higher COVIMEP can be observed in the engine operated in a DME-diesel dual fuel PCCI combustion mode, limiting an operating range of the engine. The results indicate that the DME quantity should be optimized under the different conditions to minimize the cycle-by-cycle variations and concurrently extend the operating range of the diesel-DME PCCI engines.